Dispersion of atmospheric coarse particulate matter in the San Luis Potosí, Mexico, urban area - LUIS F. PINEDA-MARTÍNEZ (Atmósfera, 2014)
Atmospheric pollution in urban areas of Mexico has become a serious problem. The study of spatio-temporal evolution of concentrations of particulate matter is an important issue. A total of 188 samples were randomly collected at 24-hour running time within the period from May 2003 to April 2004 for the San Luis Potosí urban area, located in the central-north part of Mexico, using quartz fiber filters. A series of numerical modeling experiments were conducted for the same period of measurements to investigate particulate matter (PM) concentrations in the above-mentioned urban area. Although there is a considerable annual variability in the atmospheric circulation, the analysis of results indicates preferential seasonal circulation patterns: southwesterly winds during winter and southeasterly during summer. High concentration values of particulate matter were closely associated to local characteristics of the atmospheric circulation. A net transport from the industrial zone into the urban area is one of most important outcomes of the investigation.